Socialization of Planning Implementation in Priority Areas Untia Makassar New Town - Marly Valenti Patandianan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Untia is an area provided by the government for fishing residents who were relocated from Lae-Lae Island because this island is being looked at and will be planned to become a tourist island. The government rebuilt the Untia location as a new city area with maritime characteristics, then the provincial government merged the three villages in two sub-districts into a new city unit with the same regional characteristics. The purpose of this service activity is to provide an understanding of the Untia community regarding the evaluation of the implementation of planning in the Untia New Town Priority Area, Makassar City. The method of carrying out the activities is carried out with an initial survey at the location and discussions with the community. The result of this activity is a tourism development strategy in the New Town Untia Priority area